PERAN PENDIDIKAN DALAM MENCERDASKAN MASYARAKAT - Wa Ode Murima La Ode Alumu (IAIN Ternate, 2019)
Education is an instrument for development and empowering society, wich should be prominently laid on the endewors to in crease faith (iman), piety ( taqwa), as well as morals ( akhlaq). Here, the religion led to be a basis for establishing welfare society on the earth, and for securing hehe after-life. As a consequence, the development of science and technology, on the other direction, must be persistently harmonized with those religious values. Within such relationship, religion is required as a principal mean for directing the development of on the use of science and technology